The Effect of High-Intensity Interval Training on Physical Parameters, Metabolomic Indexes and Serum Ficolin-3 Levels in Patients with Prediabetes and Type 2 Diabetes - Liu, Xiaochen; Wang, Gaifeng (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background Exercise benefits people with abnormal glucose metabolism, and serum ficolin-3 levels have been reported to be associated with diabetes. However, no relevant study has discussed the relationship between high-intensity interval training (HIIT) and ficolin-3 in a Chinese population.Objective To compare the effect of HIIT and moderate-intensity continuous training (MICT) on blood pressure, glucose control, the lipid profile and the serum ficolin-3 level in patients with prediabetes and type 2 diabetes (T2D).Methods We recruited 145 patients with prediabetes and 196 T2D patients from March to June 2018. All participants were randomly grouped into HIIT and MICT groups. HIIT consisted of progressing to twelve 1-min bouts at 90% maximal aerobic capacity (1 min recovery), and MICT consisted of progressing to 20 min at 65% maximal aerobic capacity. ˙VO2peak, body composition, blood pressure, glucose, the lipid profile and the serum ficolin-3 level were measured before and after three weeks of training.Results After 3 weeks of training, participants in both the HIIT and MICT groups had significantly lower SBP, BMI, waist circumference, % body fat, and serum levels of FPG, TC, TGs, UA and ficolin-3, as well as increased vital capacity and VOmax. Additionally, the patients in the HIIT group still had significantly lower levels of 2hPG and LDL-C, regardless of prediabetes or diabetes status. After comparing the differences in the variation in parameters between the HIIT and MICT groups, we found that HIIT could help patients with prediabetes or diabetes acquire better effects of treatment in regard to anthropometry, blood pressure, glucose control, UA and ficolin-3 levels than MICT. Finally, the patients in the HIIT group had a lower rate of loss to follow-up and a higher rate of session attendance.Conclusions Both HIIT and MICT were beneficial exercise strategies for health in patients with prediabetes or T2D. However, HIIT is a more time-efficient strategy and could lower the serum level of ficolin-3 in patients after 3 weeks of training.
Keywords: HIIT; MICT; ficolin-3; prediabetes; type 2 diabetes